Correction: In-school eyecare in special education settings has measurable benefits for children's vision and behaviour. - S A Black; E L McConnell; L McKerr; J F McClelland; J A Little; K Dillenburger; A J Jackson; P M Anketell; K J Saunders (PLoS ONE, 2019)
[This corrects the article DOI: 10.1371/journal.pone.0220480.].